Three Concepts of Internationalism in the Global South: Solidarism, Pluralism, and Developmentalism - Wu, Wenbo (Global South Review, 2023)
Throughout modern history, internationalism has been one of the most powerful forces that drives global political changes. While existing research focuses exceptionally on liberal internationalism, studies devoted to internationalism beyond its liberal and Western forms remain relatively scant. Building on a conception that perceives internationalism as a form of human practices, this article explores the evolution of the concept of internationalism in the Global South through a series of political practices from the drafting of the Universal Declaration of Human Rights in 1948 and the 1955 Asian-African Conference in Bandung to the proposal of the New International Economic Order in 1974 and the BRICS’s contestation over NATO’s Libyan intervention in 2011. It is argued that the normative core of internationalism in the Global South is constituted of three major components – pluralism, solidarism, and developmentalism, each in its particular form. Taken together, it envisions an international order rooted in the solidarity of the post-colonial peoples based on their shared colonial past, underpinned by a pluralistic outlook of political life, and places emphasis on redistributive justice in structuring the international economic order. Though some argue that with the rise of the BRICS countries, there will be a revival of Global South internationalism, this article concludes that this is not likely to happen at present.